Optimization-based decision support system for accurate earthquake epicenter determination - Roma Sinta Simbolon; Methodius Tigor (Vertex, 2021)
Accurate determination of earthquake epicenters is vital for effective disaster response and risk mitigation. This research proposes a Decision Support System (DSS) that leverages optimization techniques to enhance earthquake epicenter determination accuracy. The DSS combines seismic data processing, geospatial analysis, and advanced optimization algorithms to pinpoint epicenters with high precision. The study presents a mathematical formulation to minimize the misfit between observed and theoretical travel-time data using optimization algorithms. A numerical example showcases the DSS's effectiveness in accurately localizing seismic events. The research demonstrates that the DSS outperforms traditional methods, providing valuable insights for seismic monitoring agencies and disaster response teams. The DSS offers a promising solution for real-world applications, contributing to community safety and disaster preparedness in seismic-prone regions